Basic Statistics - Maxwell, A. author. aut Link
126 p. 2 illus.
Keywords: For many years now I have been required to give a series of elementary lectures on statistics to medical students about to undertake a postgraduate course in psychiatry. The declared aim of the course, for which very limited time was available, was to provide the students with some initial understanding of the statistical terminology and elementary techniques to which other teachers, in particular psychologists and sociologists, would be likely to refer in the course of their lectures. The task was tricky for two reasons. In the first place most of the students involved, despite their best intentions, had forgotten their school mathematics, and secondly no textbook existed at the right level of difficulty which contained examples appropriate to these students' needs and experience. The present book was written to fill the gap. Though pri marily intended for psychiatrists, the book should prove very useful to any student of the behavioural sciences who wants a simple introductory course on the principles of experimental design and data analysis. It must be one of the simplest text books on elementary statistics ever written. I am indebted to the literary executor of the late Sir Ronald A. Fisher, F.R.S., to Dr Frank Yates, F.R.S., and to Oliver & Boyd Ltd for permission to reprint Tables 3 and 5 from their book Statistical Tables for Biological, Agricultural and Medical Research.